Injunctions against false advertising - Florian Baumann; Alexander Rasch (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2019)
Rules of consumer protection or fair competition can be publicly or privately enforced. We consider the possibility of false advertising by a firm in duopolistic competition where consumers can be distinguished according to whether or not they form rational beliefs about the trustworthiness of advertising claims. We compare private and public law enforcement in the form of the demand for injunctions against false advertising. From a welfare perspective, we show that it can be optimal either to have the private entity (the competitor/a consumer protection agency) or the government agency as plaintiff, where the optimal regime depends on the share of naïve consumers and the level of trial costs in a non-trivial way.
Keywords: K41; K42; L13; L15; 330; injunction suits; false advertising; law enforcement; naïve consumer; product differentiation